Evaluasi Efektivitas Rain Barrel dalam Pengendalian Limpasan Permukaan di Kawasan Perumahan Modern di Kota Bogor - Muhamad Demirel Prasetya; Doddi Yudianto; Willy Willy (JURNAL SUMBER DAYA AIR, 2025)
Bogor City, with a population of approximately 1,064,000 in 2022 and an annual growth rate of 2.01%, faces increasing pressure to meet housing demands. To accommodate this need, one modern residential development in the area has undergone extensive expansion. A previous assessment indicated that the development of a 10.75-hectare residential area in this neighborhood could increase peak discharge by approximately 24.74% for the 2-year return period and 16.67% for the 5-year return period.Based on these findings, this study aims to evaluate the effectiveness of Low Impact Development (LID) measures, specifically the use of rain barrels, in mitigating the hydrological impacts of land-use changes. Simulations were conducted using the Storm Water Management Model (SWMM) to: (1) analyze changes in peak discharge and runoff volume before and after development; (2) design the residential drainage system while testing different rain barrel capacities; and (3) evaluate the effectiveness of rain barrels in reducing peak discharge and runoff.Simulation results indicate that the installation of two rain barrels per household, each with a diameter of 1.41 m and a height of 1.19 m, can reduce peak discharge by 19.66%, approaching pre-development conditions. However, total runoff volume remains higher than baseline levels, suggesting that additional LID strategies are necessary for more comprehensive flood mitigation. These findings underscore the potential of rain barrels as an effective tool for urban runoff management and provide practical guidance for optimizing their implementation in similar residential developments.